Pneumocystis jirovecii pneumonia in patients treated for systemic autoimmune disorders: a retrospective analysis of patient characteristics and outcome. (2nd September 2020) - Verhaert, M; Blockmans, D; De Langhe, E; Henckaerts, L
Abstract : Objectives : Pneumocystis jirovecii is an opportunistic fungus. Pneumocystis jirovecii pneumonia (PJP) is well known in the human immunodeficiency virus (HIV)-infected population, but in non-HIV-related immunosuppressed patients, risk factors are largely unknown. We studied the characteristics and outcome of patients treated for systemic autoimmune disorders infected with P. jirovecii, aiming to clarify risk stratification to guide prophylaxis. Method : Clinical charts collected between 2010 and 2016 at the University Hospital of Leuven (Belgium) were reviewed. Information on type of systemic disorder, organ involvement, immunosuppressant use, and comorbidity was collected, and laboratory results were consulted. Results : In total, 39 cases of non-HIV PJP were retrieved, 24 of whom had pre-existing pulmonary disease. All were on immunosuppressant medication at the time of infection, the majority (36/39) taking glucocorticoids, with a median dose of 16 mg methylprednisolone over the past 3 months. Of the 39 cases, 21 were admitted to the intensive care unit and mortality reached 35%. Age and pulmonary disease correlated positively and methotrexate use negatively with mortality. When applying current prophylactic strategies to our cohort, 50% of infections could theoretically have been prevented. Conclusion : PJP is a rare but relevant clinical problem when caring for immunosuppressed patients with autoimmune systemic disorders. Pulmonary disease and age are risk factors for acquiring the infection and carry a worse prognosis. More studies are needed to further define prophylactic criteria.